Literatur Review : Pendekatan Keperawatan Transkultural Dalam Homecare Gangguan Jiwa Oleh Caregiver - Arini, Larasuci; Syukur, Yarmis; Syarli, Setiadi; Firmani, Firmani (Pustaka Galeri Mandiri, 2025)
This literature review explores the application of transcultural nursing approaches in the homecare of individuals with mental disorders by caregivers. The findings reveal that culturally sensitive care significantly enhances communication, trust, and therapeutic outcomes. Training caregivers in cultural competence is essential to meet the diverse needs of patients, reduce stigma, and improve adherence to treatment. The study highlights the importance of systemic support, family involvement, and continued education to develop inclusive and humane mental health care practices.